Profitability Ratio Analysis of the Leather Tanning Industry With Loan Capital Structure Interest System - Kurniawan, Aceng (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2022)
The leather tannery industry in Sukanggang Garut declined in number due to bankruptcy, which was caused by declining business profitability. The profitability of tanned leather craftsmen was initially 6.5 million rupiah to 2.3 million rupiah per ton of raw materials. The decline in the level of profitability was due to changes in the capital structure, with many using loan capital with an interest system compared to own capital. The purpose of this study was to determine the effect of interest system loans on the profitability of the leather industry. This study uses the method of profitability ratio analysis. From the research results, the ratio of GPM, NPM and ROI decreased along with the increase in the number of loans with an interest system. GPM continued to decline from 39.02 percent to 35.37 percent. NPM continued to decline from 15.26 percent to 8.26 percent. ROI decreased from 18.00 percent to 8.05 percent. ROE actually increases with the increase in the number of loans in its capital structure.